Evaluasi Sistem Proteksi Kebakaran pada Bangunan Hotel UNY 5 Lantai Di Yogyakarta - Muhammad Heri Zulfiar; Akhid Gunawan (Semesta Teknika, 2018)
Fire is an event that causes many losses. Fire in multi-storey buildings will cause many losses. Some fire events in comersial multi-storey buildings can be used to be mitigation reference to decrease fire risk. Hotel is one of comersial buildings that has a safety standard to the occupants. One of the protection form is making protection for fire hazard. This research is conducted at UNY Hotel located at Karangmalang Street Caturtunggal Depok Sleman Yogyakarta. By this research, hopefully UNY Hotel can be the reference of fire protection system for the others comersial buildings in Yogyakarta.The purpose of this research is to assess the completeness of facilities and infrastructure of fire protection system that available at UNY Hotel. The method is by observation process and assessment of 4 parameters of reliability of building safety system, that are site completeness, rescue device, active protection, and passive protection with reference to Regulation of Minister of Public Works Number 26/PRT/M/2008 about Technical Requirement of Protection System Fire on Building and Environment Building and Fire Safety Building Inspection Guidebook (Pd-T-11-2005-C) from Research and Development Agency of Ministry of Public Works and several related Indonesian National Standards.The results of the Reliability Building Safety System is 91,60 which means the value of the reliability of the building at UNY Hotel is good. So, UNY Hotel building can be used optimally and building users get protection from fire building hazard.